SISTEM NILAI ORGANISASI PADA PERUSAHAAN KELUARGA BATAK TOBA - , PAULUS AGUS MALA SIHOMBING, Prof. Dr. Asip F. Hadipranata ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This research proposed to explain the system of values prevailing in the family organization, which has the same cultural values as the Toba Batak. This study used qualitative methods with an ethnographic-case study approach. Ethnography was used to explain and interpret the cultural, or social group, which in this study, the culture of Toba Batak. Case studies were used to describe a case associated with the system in the family business. Data collected in the form of primary and secondary data. The primary data obtained through in-depth interviews and self-reports, while the secondary data obtained from observations and interviews with significant others. The subjects in this study amounted to three persons, consisting of one manager and two men were employed in the family company with a note that the three men were part of the family. The reason for selecting these subjects because they are families, so researchers have assumed the same value with Toba Batak family. In addition, selection based on hierarchical top and middle management firm, will assist in seeing the extent to which there is shared understanding of the value system prevailing in the family organization. Data analysis was carried out in accordance with qualitative methods of data processing, namely open coding, axial coding and selective coding. The results explain that in this study recognized that success is marked on the amount of material is something that has passed through the teaching of values and family education, especially parents. Cultural value is a value particularly in subjects and considered as a value that has been tested from all generations. Based on cultural values, organization then formed into result oriented. The assumption of these values, set off from the consciousness of the subject that the success of the Toba Batak, can only be seen from the material produced, in the form of individual and corporate wealth grow.